The role of the army in the destruction of Yugoslavia - Radinović, Radovan (Napredak, 2021)
Yugoslavia was destroyed through the concerted effort of domestic forces of the seceding republics and foreign factors, embodied by the entirety of the Western world. Although the USA undoubtedly supported the West, in the early stages of the process, they favored the preservation of Yugoslavia. The country with the leading role in the destruction of Yugoslavia was Germany. The causes of the disappearance of Yugoslavia from the political map of Europe and the world were numerous: economic, social, political, geopolitical, etc. In this article we focus on the military component, that is, the role of the Yugoslav People’s Army in the destruction process. We consider various factors which brought to the situation in which the YPA proved itself utterly unsuccessful and ineffective in defending itself from destruction from the inside. We also look at the opportunities with which the YPA was presented, which it failed to seize. These choices lead the country and its citizens into a bloody civil war with countless victims and great destruction. The YPA itself was finally pilloried for its ultimately disastrous attempts to protect the state from aggressive forces within.
Keywords: destruction of Yugoslavia; armed secession; armed aggression from within; YPA; territorial defense; high command; General Chief of Staff; military offensive